Utilizing Behavior Change Techniques to Elicit Adherence to Clinical Practice Guidelines - Ferreira, Daniel (Frontiers in Public Health, 2017)
Abstract Introduction: Two 2-day continuing education seminars were developed to address the orthopedic physical therapy deficits in the country of Guyana. Material was presented in a way to address all stages of behavior change. Methods: Surveys evaluating pre- and post-seminar knowledge was evaluated. Chart reviews to establish adherence to clinical practice guidelines were performed. Results: Pre-seminar surveys revealed minimal knowledge of clinical practice guidelines which was consistent with pre-seminar chart review data. Post-seminar data indicate improvements in both knowledge and adherence to guidelines. Discussion: A brief series of two 2-day seminars utilizing behavior change strategies to improve adherence to clinical practice guidelines shows promise for countries and regions that rely on international health volunteers to provide clinical instruction. Because this study is limited to one situation, further studies with longer follow-up in a variety of clinical settings are recommended to support generalizability of findings.